Combined DOG1 and Mammaglobin Immunohistochemistry Is Comparable to ETV6-breakapart Analysis for Differentiating Between Papillary Cystic Variants of Acinic Cell Carcinoma and Mammary Analogue Secretory Carcinoma. (April 2017) - Said-Al-Naief, Nasser; Carlos, Roman; Vance, Gail H.; Miller, Caroline; Edwards, Paul C.
Background . We investigated the reliability of combined DOG1 and mammaglobin immunohistochemistry compared with ETV6 fluorescence in situ hybridization (FISH) in the assessment of salivary tumors previously diagnosed as acinic cell carcinoma (ACC). Ultrastructural features of cases reclassified as mammary analogue secretory carcinoma (MASC) were assessed by transmission electron microscopy (TEM). Methods . Immunohistochemical (IHC) reactivity to DOG1 and mammaglobin was validated against FISH targeting the ETV6 gene in all 14 cases. Results . Three cases with papillary cystic histomorphology previously diagnosed as ACC were revised to MASC. TEM features of the ETV6 rearrangement-positive MASC cases showed large numbers of secretory granules with extrusion into the intercellular spaces, well-developed endoplasmic reticulum, lipid-laden vacuoles, well-formed microvilli, and large lining cystic spaces. Conclusions . Combined DOG1 and mammaglobin immunohistochemistry is comparable to ETV6 -breakapart analysis for differentiating between papillary cystic variants of ACC and MASC.